Volume 3: Pipeline and Riser Technology 2012
DOI: 10.1115/omae2012-84256
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Behavior of Tensile Tests for GFRP Filament Wound Pipes With Two Different Sectional Areas Regarding High Temperature

Abstract: In this work were compared two types of filament wound pipe specimens to know the variation in stress and strain regarding to the cross sectional area variation at 65° C according to the standards. The groups are named as G1 and G2, respectively with the G1 having 63.5mm of internal nominal diameter, and the G2 having 76.2mm. Both groups had 800mm of length, 3.5 mm of wall thickness and tabs laminated with 200 mm length. It was applied a monotonic load with a rate of 6.35 mm/minute. Three strain gages were pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In both this study and the literature, significant differences were found between the results of tensile (or compressive) tests for 180-and 600-mm-long specimens [1,24,52].…”
Section: Conclusion and Remarksmentioning
confidence: 75%
See 1 more Smart Citation
“…In both this study and the literature, significant differences were found between the results of tensile (or compressive) tests for 180-and 600-mm-long specimens [1,24,52].…”
Section: Conclusion and Remarksmentioning
confidence: 75%
“…The first paper in this series covered the preliminary analysis of acoustic emission behavior for the same sample typology [1]. In this work, the correlation between the three winding angles was investigated, and the variation of their elastic properties was used as a control parameter throughout the research project.…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…Thus, for each design of great complexity is necessary to evaluate the typology of the composite that will be used. In contrast, structural members and components need their evaluation during their serviceable life, because of critical conditions of use environmental, seismic, or fatigue, which could cause injuries in humans [1][2][3][4][5] The previous articles [6,7] showed the behavior of the acoustic signals over filament wound composite pipes, and how the position of the signal source or, in this case, the damage occurrence could be interfered with by the interlacing of opposites filaments of roving, regarding the lamination path. Three types of This paper presents the continuation of prior studies, which comprised the verification of the variation that occurred in the dynamic elastic modulus (E 11 ) regarding the three angular winding laminations described, in comparison with an isotropic material.…”
Section: Introductionmentioning
confidence: 99%